Hubungan Tingkat Pengetahuan Dan Usia Calon Pengantin Putri dengan Persiapan Kehamilan Pertama di KUA Kecamatan Tanjung Agung Kabupaten Muara Enim Tahun 2023 - Yeni Yusita; Sabtian Sarwoko; Berita Afriani (Pusat Riset dan Inovasi Nasional, 2024)
Facts show that more than 350,000 worldwide die every year due to complications of pregnancy and childbirth. Indonesia's National Maternal Mortality Rate (MMR) in 2017 and 2019 did not change, namely 305 per 100,000 live births. Prospective brides and grooms are a strategic target group in efforts to improve their health before pregnancy. The aim of the research is to determine the relationship between the level of knowledge and age of the prospective bride and groom with preparation for their first pregnancy in KUA, Tanjung Agung District, Muara Enim Regency. The research method is descriptive analytical with a cross sectional approach. This research began in April – June 2023 at KUA, Tanjung Agung District, Muara Enim Regency. Sampling technique using a total sampling of 50 respondents. The data collection method in this research uses a questionnaire. Data analysis used the Chi-Square test. The results of this study show that there is a relationship between knowledge (p= 0.000) and age (p= 0.004) of the prospective bride and groom and preparation for their first pregnancy in KUA Tanjung Agung District, Muara Enim Regency. The conclusion is that knowledge and age are related to preparation for the first pregnancy.